Advancements in Photocatalysis: Applications in Environmental Remediation - Neha Sahu (International Journal of Photochemistry and Photochemical Research, 2024)
The study of radioluminescence, a phenomenon where materials emit light upon exposure to ionizing radiation, has expanded significantly in recent years, finding applications in various fields, including environmental remediation, radiation detection, and dosimetry. This paper reviews recent advancements in radioluminescent technologies, particularly focusing on Radioluminescent Isotope Cells (RLICs) and semiconductor colloidal quantum dots (cQDs). The use of RLICs, particularly those based on 63Ni, demonstrates enhanced energy conversion efficiency through optimized photon transport interfaces, achieving a significant output power increase compared to traditional structures. Furthermore, the study highlights the potential of RLICs in extreme environments, owing to their long lifespan, high stability, and energy density.Additionally, the performance of semiconductor cQDs, specifically Multi-Shell (MS) and Core/Shell (CS) structures, is explored for radiation detection. MS cQDs exhibit superior resistance to ionizing radiation, showcasing a better recovery of radioluminescence signals compared to their CS counterparts. This resilience to radiation makes them promising candidates for scintillation dosimetry in various applications, including medical and industrial settings.Moreover, Gd-doped sol-gel silica glass is investigated for its radiation-induced emission characteristics, establishing its suitability for dosimetry in radiotherapy. The emitted light's intensity and decay characteristics provide crucial insights into dose measurements, essential for therapeutic applications.Overall, the advancements in radioluminescent materials and technologies demonstrate significant potential in enhancing radiation detection and measurement systems, with implications for environmental monitoring and medical applications. This review not only underscores the innovative strategies employed to improve the performance and stability of these materials but also paves the way for future research in the field of radioluminescence and its diverse applications.
Keywords: Quantum dot; Radioluminescence; isotope cells; s dosimetry; silica glass